Nanobiotechnology-mediated regulation of reactive oxygen species homeostasis under heat and drought stress in plants - Bao, Linfeng; Liu, Jiahao; Mao, Tingyong; Zhao, Linbo; Wang, Desheng; Zhai, Yunlong (Frontiers in Plant Science, 2024)
Global warming causes heat and drought stress in plants, which affects crop production. In addition to osmotic stress and protein inactivation, reactive oxygen species (ROS) overaccumulation under heat and drought stress is a secondary stress that further impairs plant performance. Chloroplasts, mitochondria, peroxisomes, and apoplasts are the main ROS generation sites in heat-and drought-stressed plants. In this review, we summarize ROS generation and scavenging in heat-and drought-stressed plants and highlight the potential applications of plant nanobiotechnology for enhancing plant tolerance to these stresses.